Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Machine learning for time series prediction of valley deformation induced by impoundment for high arch dams - Hang-Hang Zang; Dian-Qing Li; Xiao-Song Tang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Methoxyflavone glucosides and caffeoyl phenylethanoid glycoside from Lysionotus pauciflorus: their structures and anti-ferroptosis activity - Rena Takizawa; Tomoyo Minamizono; Daisuke Tsuji; Xiao-Jie Yan; Feng-Lai Lu; Xue-Rong Yang; Dian-Peng Li; Reiko Akagi; Yoshiki Kashiwada; Naonobu Tanaka (Journal of Natural Medicines, 2025)

Efficient Bayesian updating for deformation prediction of high rock slopes induced by excavation with monitoring data - Dian-Qing Li; Hang-Hang Zang; Xiao-Song Tang; Guan Rong (Engineering Geology, 2024)

Enhanced waste Plastics-to-Power in situ conversion through iron oxide as pseudofuel in solid oxide fuel cells - Rong Zhang; Wenting An; Yanxia Guo; Yong Jiao; Si-Dian Li; Fangqin Cheng (Fuel, 2024)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Comparative genomics of the marine bacterial genus G laciecola reveals the high degree of genomic diversity and genomic characteristic for cold adaptation - Qi‐Long Qin; Bin‐Bin Xie; Yong Yu; Yan‐Li Shu; Jin‐Cheng Rong; Yan‐Jiao Zhang; Dian‐Li Zhao; Xiu‐Lan Chen; Xi‐Ying Zhang; Bo Chen; Bai‐Cheng Zhou; Yu‐Zhong Zhang (Environmental Microbiology, 2014)
Summary To what extent the genomes of different species belonging to one genus can be diverse and the relationship between genomic differentiation and environmental factor remain unclear for oceanic bacteria. With many new bacterial genera and species being isolated from marine environments, this question warrants attention. In this study, we sequenced all the type strains of the published species of G laciecola , a recently defined cold‐adapted genus with species from diverse marine locations, to study the genomic diversity and cold‐adaptation strategy in this genus. The genome size diverged widely from 3.08 to 5.96 M b, which can be explained by massive gene gain and loss events. Horizontal gene transfer and new gene emergence contributed substantially to the genome size expansion. The genus G laciecola had an open pan‐genome. Comparative genomic research indicated that species of the genus G laciecola had high diversity in genome size, gene content and genetic relatedness. This may be prevalent in marine bacterial genera considering the dynamic and complex environments of the ocean. Species of G laciecola had some common genomic features related to cold adaptation, which enable them to thrive and play a role in biogeochemical cycle in the cold marine environments.

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)